Proses Kognitif Manusia Prespektif Al Ghazali Dan Implikasinya Pada Pengendalian Perilaku Konsumenisme Di Era Digital - Pratama, Lukman Nugraha (Journal of Sufism and Psychotherapy, 2024)
The digital era has transformed global consumer behavior, making people increasingly dependent on technology in making purchasing transactions. Along with the increasing ease of digital access, there has been a tendency for excessive consumerism among the community. This condition has created various serious problems, including personal financial crises, mental health disorders, and worrying environmental damage, so that cognitive and spiritual approaches are needed to control them. Based on these problems, this study aims to analyze human cognitive processes from Al-Ghazali’s perspective and explore its implications for controlling consumer behavior in the digital era. The methodology used is literature research with a qualitative approach, utilizing the book Kimiya’ As-Sa’adah by Imam Al-Ghazali as a primary source and various supporting literature as secondary sources, which are then analyzed using content analysis methods systematically and objectively to find the relevance of Al-Ghazali’s thoughts to the phenomenon of digital consumerism. The results of the study indicate that Al-Ghazali’s perspective on the human cognitive process views the human structure as consisting of qalb (heart), reason, lust, and anger that are mutually integrated, where the implementation of his cognitive development methods such as worship practices, spiritual learning, and contemplative observation can help consumers build resilience in facing consumer stimuli in the digital era. Based on these findings, this study recommends the need to integrate Al-Ghazali’s thoughts into the educational curriculum and the development of spiritual development programs and cognitive training to help consumers maintain self-control in facing the increasingly massive flow of digital consumerism.